FORMATION OF SPATIAL-GRAPHIC SKILLS IN CHILDREN WITH (Journal of Educational Sciences, 2019)
This article discusses the developed set of methods for the formation of spatial-graphic skills in children of senior preschool age with delayed psychical development. For the experiment, 20 children were taken at the age of 6; 10 of whom had a diagnosis of “mental retardation”, and the other 10 children had an age level of intellectual development. The experiment was carried out in two stages: the first stage - ascertaining, the study of the state of the problem of the formation of spatial-graphic skills in children of preschool age with mental retardation; the second stage is forming, carrying out experimental work with children of senior preschool age with mental retardation. Experimental verification of the effectiveness of a set of classes with games and exercises that affect the formation of spatial graphic skills in children of senior preschool age with mental retardation. According to the results of the experiment, children of older preschool age with delayed psychical development undergoing special training increased the level of awareness of spatial-graphic skills. In determining their position in space, they operated with a significant amount of verbal spatial terminology. Children learned to differentiate, generalize, and establish spatial relations between objects and objects of the surrounding reality.Key words: delayed psychical development, spatial-graphic skills, correctional and developmental work, attention, teacher-defectologist.